Analisis Kadar Vitamin C Pada Daun Katuk (Sauropus Androgynus) Segar, Direbus dan Dikukus Dengan Metode Spektrofotometri UV-Vis - Muhammad Hadi Sulhan Hadi Sulhan (Jurnal Medika Cendikia, 2019)
Katuk leaf (Sauropus Androgynus) is a kind of green leafy vegetable which has many benefits for the community, one of which is to treat heartburn, fever, earache, and yaws. Vitamins contained in Sauropus Androgynus and are useful for the body, one of which is vitamin C. Vitamin C has properties that are easily damaged against heat, and easily dissolve in water. This study aims to look at vitamin C levels in fresh, steamed and boiled Sauropus Androgynus by the UV-Vis Spectrophotometry method. Determination of vitamin C levels with this method is relatively inexpensive and good in accuracy. The results obtained with 30 samples with an average level of vitamin C in fresh Sauropus Androgynus 0.0036%, Sauropus Androgynus steamed 0, and Sauropus Androgynus boiled 0.0032%. It can be concluded that the vitamin C levels of boiled Sauropus Androgynus do not decrease significantly, compared to the levels of Vitamin C on freshSauropus Androgynus. the result is different from the Sauropus Androgynus that are steamed vitamin C levels become zero mg